1998
DOI: 10.1002/(sici)1520-6661(199807/08)7:4<177::aid-mfm3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of arginine vasopressin suppression of ovine fetal lung fluid secretion: Lack of V2-receptor effect

Abstract: Fetal lung liquid production is essential for in utero pulmonary development, and the resorption of lung liquid at birth facilitates neonatal transition. Lung liquid also contributes importantly to amniotic fluid volume. Factors that influence lung liquid production/resorption may, therefore, impact fetal pulmonary growth and development as well as amniotic fluid homeostasis. Arginine vasopressin (AVP) inhibits fetal lung liquid production and facilitates lung liquid resorption. In view of studies administerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[21][22][23] However, the mechanism involved remains uncertain. In fetal sheep, Albuquerque et al 24 found no evidence that the vasopressin-2 receptor mediated a reduction in lung fluid production; they suggested the effect was instead mediated by the vasopressin-1 receptor. In the neonatal rat, on the other hand, Guetta et al 25 showed that the vasopressin-2 receptor regulates the increase in active sodium transport and alveolar fluid clearance from the lung.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] However, the mechanism involved remains uncertain. In fetal sheep, Albuquerque et al 24 found no evidence that the vasopressin-2 receptor mediated a reduction in lung fluid production; they suggested the effect was instead mediated by the vasopressin-1 receptor. In the neonatal rat, on the other hand, Guetta et al 25 showed that the vasopressin-2 receptor regulates the increase in active sodium transport and alveolar fluid clearance from the lung.…”
Section: Discussionmentioning
confidence: 99%